2009
DOI: 10.1124/jpet.108.149807
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Deferoxamine Provides Increased Brain Exposure and Significant Protection in Rat Ischemic Stroke

Abstract: Deferoxamine (DFO) is a high-affinity iron chelator approved by the Food and Drug Administration for treating iron overload. Preclinical research suggests that systemically administered DFO prevents and treats ischemic stroke damage and intracerebral hemorrhage. However, translation into human trials has been limited, probably because of difficulties with DFO administration. A noninvasive method of intranasal administration has emerged recently as a rapid way to bypass the bloodbrain barrier and target therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(129 citation statements)
references
References 37 publications
5
119
0
Order By: Relevance
“…Several reports confirm the positive outcome of nose-to-brain delivery not only for drug molecules with various molecular weights [11,12] but also for living cells [13,14]. Hanson et al (2009) [11,12] reported that INA targets deferoxamine to the brain and reduces systemic exposure, and that intranasal deferoxamine prevents and treats stroke damage after middle cerebral artery occlusion in rats.…”
Section: Drug Instillationmentioning
confidence: 90%
See 1 more Smart Citation
“…Several reports confirm the positive outcome of nose-to-brain delivery not only for drug molecules with various molecular weights [11,12] but also for living cells [13,14]. Hanson et al (2009) [11,12] reported that INA targets deferoxamine to the brain and reduces systemic exposure, and that intranasal deferoxamine prevents and treats stroke damage after middle cerebral artery occlusion in rats.…”
Section: Drug Instillationmentioning
confidence: 90%
“…Hanson et al (2009) [11,12] reported that INA targets deferoxamine to the brain and reduces systemic exposure, and that intranasal deferoxamine prevents and treats stroke damage after middle cerebral artery occlusion in rats. On the other hand, Danielyan and collaborators (2001) [13,14] have revealed noninvasive intranasal delivery of stem cells to the rat brain for the first time,…”
Section: Drug Instillationmentioning
confidence: 99%
“…Recent reports confirm the positive outcome of noseto-brain delivery not only for drug molecules with various molecular weights (Hanson et al, 2009;Yang et al, 2009), but also for living cells (Danielyan et al, 2009;Danielyan et al, 2011). Nanoemulsion (NE) formulation offers an improvement to nose-to-brain drug delivery since they are able to protect the encapsulated drug from biological and/or chemical degradation, and extracellular transport by P-gp efflux proteins.…”
Section: Introductionmentioning
confidence: 91%
“…Nasal tissues from two untreated control rats were processed in the same manner as the treated tissues. Three driving pressures (10,20, and 30 psi) of the POD device were tested. Within 5 min of dosing, the animal was euthanized.…”
Section: Histopathologic Examination Of Rat Nasal Cavitymentioning
confidence: 99%
“…A variety of nasal delivery methods are typically used in studies investigating nose-tobrain delivery in rodents, but very few studies specifically and consistently deposit drug on the olfactory epithelium. The most commonly used nasal administration modes are nose drops (18)(19)(20)(21), in which the animal is placed on its back in a supine position while liquid drops are snorted into the nasal cavity, or inserting a soft catheter connected to a microsyringe into the nasal cavity and applying a volume of drug a set distance into the nasal cavity from the naris (11,22). These methods may effectively deliver drug to the nasal cavity; however, they tend to involve a large dose volume resulting in saturation of both the respiratory and olfactory epithelium.…”
Section: Introductionmentioning
confidence: 99%